Tranzzl!n9o: A Human Computation Approach to English Translation of Internet Lingo - Hong, Ming-Tung; Hsu, Yung-Jen (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
Lingo is an emerging language on the Internet. Providing a standardized definition remains difficult due to continuous changes made to its nature. We proposed Tranzzl!n9o, a crossword puzzle game for engaging crowds to translate Internet lingo. Players provide explanations for lingo in parallel and iteratively verify the explanations from other players. Crowd-sourced translations are very informative containing explanations as well as lingo usage.